Magnesium titanate-containing catalyst, preparation method and application thereof, and method for producing hydrogen through ammonia decomposition

By using a magnesium titanate-containing catalyst and combined with sol-gel preparation technology, the existing ammonia decomposition catalysts are solved inadequate activity and high cost at low temperatures, and an efficient and economical ammonia decomposition catalytic effect is achieved.

CN119897128AActive Publication Date: 2025-04-29CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202311410669.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-27
Publication Date
2025-04-29
Estimated Expiration
2043-10-27

AI Technical Summary

Technical Problem

The existing ammonia decomposition catalysts have poor ammonia decomposition activity at low temperatures and are relatively high in cost, especially the high cost of precious metal catalysts and insufficient low temperature activity.

Method used

A magnesium titanate-containing catalyst is used, which consists of a magnesium titanate support and active components containing precious metals and non-precious metals. It is prepared by the sol-gel method to adjust the electron transfer ability and adsorption strength of the catalyst and improve the ammonia decomposition conversion rate.

Benefits of technology

It realizes efficient catalytic ammonia decomposition at low temperatures, improves the ammonia decomposition conversion rate, reduces the amount of precious metals, saves costs, and simplifies the preparation process, improves the repeatability and feasibility of large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004518074730000191
    Figure BDA0004518074730000191
  • Figure BDA0004518074730000202
    Figure BDA0004518074730000202
Patent Text Reader

Abstract

The invention relates to the field of ammonia decomposition catalyst preparation, and discloses a magnesium titanate-containing catalyst, a preparation method and application thereof, and a method for producing hydrogen through ammonia decomposition. The magnesium titanate-containing catalyst contains a magnesium titanate carrier and active components, the active components comprise noble metals and non-noble metals, and the non-noble metals are selected from group VIII metal elements; on the basis of the total weight of the catalyst and in terms of metal elements, the content of the active component is 0.5-20 wt%; wherein in terms of metal elements, the mass ratio of the precious metal to the non-precious metal is 1: (5-25). The catalyst has high activity, is applied to hydrogen production through ammonia decomposition, and has high ammonia decomposition conversion rate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of preparation of ammonia decomposition catalysts, and in particular to a magnesium titanate-containing catalyst, a preparation method and application thereof, and a method for producing hydrogen by decomposing ammonia. Background Art

[0002] At present, hydrogen almost comes from the catalytic steam reforming of fossil fuels, which is also the most mature commercial hydrogen production technology. However, the hydrogen produced by catalytic reforming will be accompanied by impurity gases such as carbon monoxide and carbon dioxide, and cannot be directly used as fuel cell fuel. Therefore, using hydrogen-rich carrier ammonia as a raw material for carbon-free hydrogen production is an efficient, clean and safe hydrogen production technology. In order to achieve safe and green hydrogen production, it is particularly important to develop catalysts that can efficiently catalyze the decomposition of ammonia. At present, ammonia decomposition catalysts are divided into precious metal catalysts with ruthenium and platinum as active components and non-precious metal catalysts with iron and nickel as active components.

[0003] At present, ruthenium is the catalyst with the highest catalytic ammonia decomposition activity, but it is relatively expensive and the cost of the prepared catalyst is high, so it is very important to improve the utilization rate of ruthenium atoms. Studies have found that the stability of ruthenium is highly correlated with the acidity and alkalinity of the carrier and the conductivity. For this reason, extensive research has been conducted on precious metal ammonia decomposition catalysts. For example, CN115920942A discloses a Ru-based catalyst including a ZIF-8 carrier or a ZIF-67 carrier coated with MOF-74, wherein the active component is ruthenium, and the auxiliary component is one or more of barium, lanthanum, and cesium. A combination of the components. Although the reaction temperature is reduced to 500 ° C, due to the poor dispersion of the auxiliary on the carrier surface, large particles are easily formed, resulting in poor ammonia decomposition activity at low temperatures. Summary of the invention

[0004] The purpose of the present invention is to overcome the problem that the activity of the existing ammonia decomposition catalyst needs to be further improved, and to provide a magnesium titanate-containing catalyst, a preparation method and application thereof, and a method for producing hydrogen by decomposing ammonia. The catalyst has high activity, is applied to the production of hydrogen by decomposing ammonia, and has a high ammonia decomposition conversion rate.

[0005] In order to achieve the above object, the present invention provides a magnesium titanate-containing catalyst, which contains a magnesium titanate carrier and an active component, wherein the active component includes a noble metal and a non-noble metal, and the non-noble metal is selected from metal elements of Group VIII; based on the total weight of the catalyst, the content of the active component is 0.5-20% by weight in terms of metal elements;

[0006] Wherein, calculated on the basis of metal elements, the mass ratio of the precious metal to the non-precious metal is 1:5-25.

[0007] A second aspect of the present invention provides a method for preparing a magnesium titanate-containing catalyst, the method comprising the following steps:

[0008] S1, dissolving a titanium source in an alcohol-glacial acetic acid mixed solution to obtain a solution A;

[0009] S2, dissolving the magnesium source in an alcohol-glacial acetic acid mixed solution to obtain solution B;

[0010] S3, adding solution B to solution A, and then treating to obtain a sol, wherein the pH of the sol is 1.5-5;

[0011] S4, drying and first calcining the sol obtained in step S3 to obtain a magnesium titanate carrier;

[0012] S5. Loading active components on a magnesium titanate carrier, wherein the active components include noble metals and non-noble metals, and the non-noble metals are selected from Group VIII metal elements.

[0013] The third aspect of the present invention provides an application of the magnesium titanate-containing catalyst described in the first aspect or the magnesium titanate-containing catalyst prepared by the preparation method described in the second aspect in hydrogen production by decomposing ammonia.

[0014] A fourth aspect of the present invention provides a method for producing hydrogen by decomposing ammonia, the method comprising: contacting ammonia with a catalyst under conditions of ammonia decomposition;

[0015] Wherein, the catalyst is the catalyst described in the first aspect or the magnesium titanate-containing catalyst prepared by the preparation method described in the second aspect.

[0016] Compared with the prior art, the beneficial effects of the present invention include:

[0017] The magnesium titanate-containing catalyst provided by the present invention adopts magnesium titanate as a carrier, which can adjust the electron transfer ability between the active component in the catalyst and the carrier, adjust the adsorption and desorption strength of NH3 on the catalyst surface, promote the transfer of NH3 between the active site and the carrier, and improve the catalytic activity; the active component containing precious metals and non-precious metals is combined with the magnesium titanate carrier, so that the catalyst has a high ammonia decomposition activity at low temperature; and the content of the active component is controlled within the range of 1-15 weight%, which is conducive to enhancing the interaction between the active component and the carrier, and effectively weakening the interaction between the active component and the ammonia decomposition product, thereby promoting the desorption of nitrogen and hydrogen, and finally making the catalyst have excellent catalytic performance.

[0018] The catalyst provided by the invention has low precious metal content, controls raw material costs, has simple preparation process, good repeatability, and is easy to carry out large-scale production. DETAILED DESCRIPTION

[0019] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0020] In one aspect, the present invention provides a magnesium titanate-containing catalyst, the catalyst comprising a magnesium titanate carrier and an active component, the active component comprising a noble metal and a non-noble metal, the non-noble metal being selected from Group VIII metal elements; based on the total weight of the catalyst, the content of the active component is 0.5-20% by weight in terms of metal elements;

[0021] Wherein, calculated on the basis of metal elements, the mass ratio of the precious metal to the non-precious metal is 1:5-25.

[0022] In the present invention, based on the total weight of the catalyst, the content of the active component is 0.5-20% by weight, preferably 1-15% by weight, calculated as metal elements, for example, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, 30%, 31%, 32%, 33%, 34%, 35%, 36%, 37%, 38%, 39%, 40%, 41%, 42%, 43%, 44%, 45%, 46%, 47%, 48%, 49%, 50%, 50%, 51%, 52%, 53%, 54%, 55%, 56%, 57%, 58%, 59%, 5 %, 11 wt %, 11.5 wt %, 12 wt %, 12.5 wt %, 13 wt %, 13.5 wt %, 14 wt %, 14.5 wt %, 15 wt %, 15.5 wt %, 16 wt %, 16.5 wt %, 17 wt %, 17.5 wt %, 18 wt %, 18.5 wt %, 19 wt %, 19.5 wt %, 20 wt %, and any value in the range formed by any two of these values. Controlling the content of the active component within the above range is beneficial to enhancing the interaction between the active component and the carrier, and effectively weakening the interaction between the active component and the ammonia decomposition product, thereby promoting the desorption of nitrogen and hydrogen.

[0023] The total content of each component of the catalyst of the present invention is 100%.

[0024] In the present invention, the mass ratio of the precious metal to the non-precious metal is 1:5-25, preferably 1:10-20, and can be, for example, 1:5, 1:6, 1:7, 1:8, 1:9, 1:10, 1:11, 1:12, 1:13, 1:14, 1:15, 1:16, 1:17, 1:18, 1:19, 1:20, and any value in the range formed by any two of these point values. This preferred embodiment is conducive to the dispersion of precious metals and enhances the interaction between precious metals and non-precious metals; at the same time, the amount of precious metals used is small, saving costs.

[0025] The content of active components in the catalyst of the present invention is measured by XRF method.

[0026] Preferably, the content of the noble metal is 0.03-1% by weight, more preferably 0.03-0.8% by weight. With this preferred embodiment, the catalyst of the present invention still has high ammonia decomposition activity at low temperatures when the noble metal content is low. In addition, the amount of noble metal used is small, which saves costs.

[0027] The present invention has no particular limitation on the type of the noble metal, and it can be any conventional choice in the art. Preferably, the noble metal is ruthenium and / or palladium.

[0028] The present invention has a wide range of selection for the type of the non-precious metal. Preferably, the non-precious metal is selected from at least one of iron, cobalt and nickel, preferably nickel. This preferred embodiment is conducive to the interaction between the precious metal and the non-precious metal, improves the activity of the catalyst, and reduces the activation energy of desorbing nitrogen.

[0029] A second aspect of the present invention provides a method for preparing a magnesium titanate-containing catalyst, the method comprising the following steps:

[0030] S1, dissolving a titanium source in an alcohol-glacial acetic acid mixed solution to obtain a solution A;

[0031] S2, dissolving the magnesium source in an alcohol-glacial acetic acid mixed solution to obtain solution B;

[0032] S3, adding solution B to solution A, and then treating to obtain a sol, wherein the pH of the sol is 1.5-5;

[0033] S4, drying and first calcining the sol obtained in step S3 to obtain a magnesium titanate carrier;

[0034] S5. Loading active components on a magnesium titanate carrier, wherein the active components include noble metals and non-noble metals, and the non-noble metals are selected from Group VIII metal elements.

[0035] The preparation method provided by the present invention first adopts a sol-gel method to prepare a magnesium titanate carrier, and then loads an active component on the magnesium titanate carrier, and the obtained magnesium titanate-containing catalyst has higher activity. In the preparation process of the magnesium titanate carrier, the titanium source and the magnesium source are first dissolved in an alcohol-glacial acetic acid mixed solution respectively, and the alcohol and glacial acetic acid are used as solvents together to inhibit the hydrolysis of the titanium source and improve the gel formation time; then the B solution is added to the A solution to mix the two, and the pH of the obtained sol is controlled within the range of 1.5-5, which is conducive to promoting the synergistic effect of the obtained magnesium titanate carrier and the active component, thereby improving the activity of the catalyst.

[0036] In the present invention, in S3, the pH of the sol is 1.5-5, preferably 3-5, such as 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 5, and any value in the range formed by any two of these values. This preferred embodiment is further conducive to promoting the synergistic effect of the obtained magnesium titanate support and the active component, thereby improving the activity of the catalyst.

[0037] According to the present invention, preferably, in S1, the mass ratio of the titanium source to the alcohol-glacial acetic acid mixed solution is 1:2-15, preferably 1:4-10. This preferred embodiment is conducive to the rapid formation of a uniform sol.

[0038] The present invention has no particular limitation on the type of the titanium source, which can be a conventional choice in the art. Preferably, the titanium source is a water-soluble titanium-containing compound, preferably at least one selected from tetrabutyl titanate, ethyl titanate and isopropyl titanate. The above titanium sources can all be obtained commercially, and are cheap and easy to obtain.

[0039] According to the present invention, preferably, in S2, the mass ratio of the magnesium source to the alcohol-glacial acetic acid mixed solution is 1:4-20, preferably 1:4-15. This preferred embodiment is conducive to the rapid formation of a uniform sol.

[0040] The present invention has no particular limitation on the type of magnesium source, which can be a conventional choice in the art. Preferably, the magnesium source is a soluble magnesium salt, preferably at least one selected from magnesium nitrate, magnesium sulfate and magnesium chloride.

[0041] In the present invention, the "soluble" means that the compound can be dissolved in a solvent directly or with the help of a co-solvent.

[0042] The present invention has no particular limitation on the amount of acetic acid and alcohol, and the amount of the sol with the above pH is determined. Preferably, in the alcohol-acetic acid mixed solution of S1 and S2, the mass ratio of acetic acid to alcohol is independently 1:0.1-2, preferably 1:1-2.

[0043] The alcohol of the present invention is used as a solvent to dissolve the magnesium source and the titanium source. The alcohol of the present invention has a wide selection range and can be a conventional choice in the art. Preferably, the alcohol of S1 and S2 is a C1-C5 alcohol, preferably at least one selected from methanol, ethanol and propanol.

[0044] The chemical formula of magnesium titanate is MgO3Ti. In order to make the reaction of solution A and solution B complete, the molar ratio of titanium to magnesium satisfies the above chemical formula. Preferably, the molar ratio of solution A calculated in terms of titanium element to solution B calculated in terms of magnesium element is 1:1.

[0045] According to a specific embodiment of the present invention, the B solution is added dropwise into the A solution while stirring.

[0046] The present invention has no particular limitation on the stirring rate, which can be appropriately selected according to specific circumstances, subject to the B solution and the A solution being mixed uniformly.

[0047] According to the present invention, preferably, the treatment conditions include: temperature of 30-50° C., preferably 30-40° C.; time of 0.5-10 h, preferably 0.5-8 h. This preferred embodiment is conducive to faster and better formation of sol.

[0048] Preferably, the treatment is carried out under static conditions.

[0049] The present invention has no particular limitation on the specific conditions of the drying, and the drying can be carried out according to conventional methods in the art. Preferably, in step S4, the drying conditions include: a temperature of 70-100° C. and a time of 8-48 hours.

[0050] According to the present invention, preferably, in step S4, the conditions for the first calcination include: a temperature of 600-1000° C. and a time of 2-6 hours.

[0051] According to the present invention, preferably, in S5, the active component is loaded on the magnesium titanate carrier by a co-precipitation method.

[0052] According to the present invention, preferably, the coprecipitation method in S5 comprises: mixing an aqueous solution containing an active component salt, a suspension containing a magnesium titanate carrier and an alkaline solution to obtain a solid product, and then drying and second calcining the solid product.

[0053] The present invention has no particular limitation on the order of adding the aqueous solution containing the active component salt, the suspension containing the magnesium titanate carrier and the alkaline solution in the above-mentioned mixing process of S5, and they can be added separately or together. In the embodiment of the present invention, it is preferred to add the aqueous solution containing the active component salt and the alkaline solution together to the suspension containing the magnesium titanate carrier.

[0054] According to the present invention, preferably, the reaction conditions include: temperature of 40-70°C, time of 3-8h, and pH of 8-10.

[0055] Preferably, the reaction is carried out under stirring conditions.

[0056] The present invention has no particular limitation on the stirring rate, and it can be appropriately selected according to specific circumstances to accelerate the reaction process.

[0057] Preferably, the concentration of the alkaline solution is 0.5-10 mol / L.

[0058] The present invention has a wide range of base types, and can be various bases commonly used in the art. Preferably, the base is an organic base and / or an inorganic base, preferably at least one selected from sodium hydroxide, sodium carbonate, sodium bicarbonate, potassium carbonate, potassium bicarbonate and ammonia water.

[0059] The present invention has no particular limitation on the amount of the alkaline solution, provided that the pH of the reaction is within the above range.

[0060] Preferably, the method further comprises: filtering and washing the reaction product to obtain a solid product.

[0061] The present invention has no particular limitation on the specific methods of filtering and washing, and the filtering and washing can be performed according to conventional methods in the art.

[0062] Preferably, the preparation of the suspension containing the magnesium titanate carrier comprises: dispersing the magnesium titanate carrier in water, and heating the water to 40-70° C. to obtain the suspension containing the magnesium titanate carrier.

[0063] In the present invention, the magnesium titanate carrier may be dispersed in water by conventional techniques such as stirring or ultrasound to achieve uniform mixing, and the present invention has no particular limitation on this.

[0064] According to the present invention, preferably, the active component salt includes a non-noble metal salt and a noble metal salt.

[0065] The present invention has a wide range of selections for the types of the non-precious metal salt and the precious metal salt, which can be conventionally selected in the art. Preferably, the non-precious metal salt and the precious metal salt are each independently a nitrate and / or a hydrochloride.

[0066] According to the present invention, preferably, the active component salt is used in an amount such that the content of the active component in the prepared catalyst is 0.5-20 wt %, preferably 1-15 wt %, calculated as metal element, based on the total weight of the catalyst.

[0067] According to the present invention, preferably, the non-precious metal salt and the precious metal salt are used in such an amount that, in the prepared catalyst, the mass ratio of the precious metal to the non-precious metal, calculated as metal elements, is 1:5-25, preferably 1:10-20.

[0068] The present invention has no particular limitation on the type of the noble metal, and it can be any conventional choice in the art. Preferably, the noble metal is ruthenium and / or palladium.

[0069] The present invention has a wide range of selection for the type of the non-precious metal. Preferably, the non-precious metal is selected from at least one of iron, cobalt and nickel, preferably nickel.

[0070] The present invention has no particular limitation on the drying in S5, and the drying can be carried out according to conventional methods in the art, which will not be described in detail herein.

[0071] The second calcination is not particularly limited in the present invention and can be performed according to conventional methods in the art. Preferably, the conditions of the second calcination include: a temperature of 550-780° C. and a time of 2-5 hours.

[0072] Preferably, the method further comprises: reducing the product of the second calcination to obtain a catalyst.

[0073] Preferably, the reduction conditions include: temperature of 600-800° C. and time of 1-3 h.

[0074] Preferably, the reduction is carried out in a reducing gas, which comprises hydrogen and optionally an inert gas; in the reducing gas, the volume content of hydrogen is 10-100%.

[0075] In the present invention, unless otherwise specified, the term "optionally" means containing or not containing, adding or not adding, adopting or not adopting. Specifically, an inert gas may or may not be added in the reduction step of the present invention.

[0076] Preferably, the inert gas is selected from at least one of nitrogen, helium, argon and neon, preferably nitrogen.

[0077] In the present invention, the "first" and "second" do not limit the substances and operations, but are only used to distinguish the substances introduced in different steps and the operations performed in different stages.

[0078] The third aspect of the present invention provides an application of the magnesium titanate-containing catalyst described in the first aspect or the magnesium titanate-containing catalyst prepared by the preparation method described in the second aspect in hydrogen production by decomposing ammonia.

[0079] A fourth aspect of the present invention provides a method for producing hydrogen by decomposing ammonia, the method comprising: contacting ammonia with a catalyst under conditions of ammonia decomposition;

[0080] Wherein, the catalyst is the catalyst described in the first aspect or the magnesium titanate-containing catalyst prepared by the preparation method described in the second aspect.

[0081] Although the noble metal-containing catalysts in the prior art can decompose ammonia at low temperatures, their ammonia decomposition activity is relatively poor, and the temperature of the ammonia decomposition reaction is generally not less than 550° C. The catalyst of the present invention still has high ammonia decomposition activity at low temperatures, and the ammonia decomposition temperature can be as low as 500° C.

[0082] Preferably, the conditions for decomposing ammonia include: a temperature of 500-650° C. and a volume space velocity of 5000-20000 mL / (g·h).

[0083] The present invention will be described in detail below through examples.

[0084] In the following examples, the ammonia decomposition conversion rate formula is as follows:

[0085] Ammonia decomposition conversion rate = (raw material ammonia content - product ammonia content) / raw material ammonia content × 100%.

[0086] Example 1

[0087] 1) Prepare an anhydrous ethanol-glacial acetic acid mixed solution by mixing glacial acetic acid and anhydrous ethanol in a mass ratio of 1:1.

[0088] 2) Weigh 24.1 g of tetrabutyl titanate and disperse it in 96.3 g of anhydrous ethanol-glacial acetic acid mixed solution to obtain solution A.

[0089] 3) Weigh 6.9 g of magnesium nitrate and disperse it in 27.5 g of anhydrous ethanol-glacial acetic acid mixed solution to obtain solution B.

[0090] 4) Add the above solution B dropwise into solution A while stirring, then place in a 30°C water bath and let stand for 0.5 h to obtain a sol with a pH of 3.

[0091] 5) The sol obtained in step 4) was dried at 70° C. for 24 h, and then calcined at 600° C. for 2 h to obtain a magnesium titanate carrier.

[0092] 6) Ultrasonic dispersion of 8.5g of the magnesium titanate carrier obtained in step 5) in deionized water, heated to 40°C, to obtain solution C; 3.15g of nickel chloride and 146.6mg of ruthenium chloride were dissolved in water to obtain a metal salt solution, wherein the total concentration of metal ions was 0.5mol / L; the metal salt solution and a sodium hydroxide solution with a concentration of 2mol / L were added to solution C, the pH was controlled to 8, stirred for 3h, and a precipitate was obtained. The obtained precipitate was washed, dried, and roasted at 550°C for 2h to obtain a roasted product. The roasted product was reduced with a mixed gas of hydrogen and nitrogen with a hydrogen gas volume fraction of 15% at 700°C for 3h to obtain 10g of catalyst. The catalyst composition and characteristic parameters are shown in Table 1.

[0093] Example 2

[0094] 1) Prepare an anhydrous ethanol-glacial acetic acid mixed solution by mixing glacial acetic acid and anhydrous ethanol in a mass ratio of 1:1.

[0095] 2) Weigh 25.5 g of tetrabutyl titanate and disperse it in 101.9 g of anhydrous ethanol-glacial acetic acid mixed solution to obtain solution A.

[0096] 3) Weigh 7.3 g of magnesium nitrate and disperse it in 29.2 g of anhydrous ethanol-glacial acetic acid mixed solution to obtain solution B.

[0097] 4) Add solution B dropwise into solution A while stirring, then place in a 30°C water bath and let stand for 0.5 h to obtain a sol with a pH of 3.

[0098] 5) The sol obtained in step 4) was dried at 70° C. for 24 h, and then calcined at 600° C. for 2 h to obtain a magnesium titanate carrier.

[0099] 6) Ultrasonic dispersion of 9g of magnesium titanate carrier obtained in step 5) in deionized water, heated to 40°C, to obtain solution C; dissolve 2.10g of nickel chloride and 97.7mg of ruthenium chloride in water to obtain a metal salt solution, wherein the concentration of metal ions is 0.5mol / L; add the obtained metal salt solution and a sodium hydroxide solution with a concentration of 2mol / L to solution C, control the pH to 8, stir for 3h, and obtain a precipitate. The obtained precipitate is washed, dried, and roasted at 550°C for 2h to obtain a roasted product. The roasted product is reduced with a mixed gas of hydrogen and nitrogen with a hydrogen gas volume fraction of 15% at 700°C for 3h to obtain 10g of catalyst. The catalyst composition and characteristic parameters are shown in Table 1.

[0100] Example 3

[0101] 1) Prepare a propanol-glacial acetic acid mixed solution by mixing glacial acetic acid and propanol in a mass ratio of 2:3.

[0102] 2) Weigh 26.9 g of tetrabutyl titanate and disperse it in 107.6 g of a propanol-glacial acetic acid mixed solution to obtain solution A.

[0103] 3) Weigh 7.7 g of magnesium nitrate and disperse it in 30.8 g of a propanol-glacial acetic acid mixed solution to obtain solution B.

[0104] 4) Add solution B dropwise into solution A while stirring, then place in a 30°C water bath and let stand for 1 hour to obtain a sol with a pH of 4.

[0105] 5) The sol obtained in step 4) was dried at 70° C. for 24 h, and then calcined at 600° C. for 2 h to obtain a magnesium titanate carrier.

[0106] 6) Ultrasonic dispersion of 9.5 g of the magnesium titanate carrier obtained in step 5) in deionized water, heated to 40°C, to obtain solution C; dissolve 1.05 g of nickel chloride and 48.9 mg of ruthenium chloride in water to obtain a metal salt solution, wherein the total concentration of metal ions is 0.5 mol / L; add the metal salt solution and a sodium hydroxide solution having a concentration of 2.0 mol / L to solution C, control the pH to 8, stir for 3 h, and obtain a precipitate. The obtained precipitate is washed, dried, and roasted at 550°C for 2 h to obtain a roasted product. The roasted product is reduced with a mixed gas of hydrogen and nitrogen with a hydrogen gas volume fraction of 15% at 700°C for 3 h to obtain 10 g of catalyst. The catalyst composition and characteristic parameters are shown in Table 1.

[0107] Example 4

[0108] 1) Prepare an anhydrous ethanol-glacial acetic acid mixed solution by mixing glacial acetic acid and anhydrous ethanol in a mass ratio of 1:1.

[0109] 2) Weigh 28.0 g of tetrabutyl titanate and disperse it in 112 g of anhydrous ethanol-glacial acetic acid mixed solution to obtain solution A.

[0110] 3) Weigh 8.0 g of magnesium nitrate and disperse it in 32 g of anhydrous ethanol-glacial acetic acid mixed solution to obtain solution B.

[0111] 4) Add solution B dropwise into solution A while stirring, then place in a 30°C water bath and let stand for 0.5 h to obtain a sol with a pH of 3.

[0112] 5) The sol obtained in step 4) was dried at 70° C. for 24 h, and then calcined at 600° C. for 2 h to obtain a magnesium titanate carrier.

[0113] 6) Ultrasonic dispersion of 9.9 g of the magnesium titanate carrier obtained in step 5) in deionized water, heated to 50°C, to obtain solution C. Dissolve 210.3 mg of nickel chloride and 9.7 mg of ruthenium chloride in water to obtain a metal salt solution, in which the total concentration of metal ions is 0.5 mol / L; add the metal salt solution and a sodium hydroxide solution with a concentration of 2 mol / L to solution C, control the pH to 8, stir for 3 hours, and obtain a precipitate. Wash the obtained precipitate, dry it, and roast it at 550°C for 2 hours to obtain a roasted product. Reduce the roasted product with a mixed gas of hydrogen and nitrogen with a hydrogen gas volume fraction of 15% at 700°C for 3 hours to obtain 10 g of catalyst. Catalyst composition and characteristic parameters are shown in Table 1.

[0114] Example 5

[0115] 1) Prepare an anhydrous ethanol-glacial acetic acid mixed solution by mixing glacial acetic acid and anhydrous ethanol in a mass ratio of 1:1.

[0116] 2) Weigh 26.9 g of tetrabutyl titanate and disperse it in 107.6 g of anhydrous ethanol-glacial acetic acid mixed solution to obtain solution A.

[0117] 3) Weigh 4.9 g of magnesium chloride and disperse it in 19.8 g of anhydrous ethanol-glacial acetic acid mixed solution to obtain solution B.

[0118] 4) Add solution B dropwise into solution A while stirring, then place in a 30°C water bath and let stand for 0.5 h to obtain a sol with a pH of 3.

[0119] 5) The sol obtained in step 4) was dried at 70° C. for 24 h, and then calcined at 600° C. for 2 h to obtain a magnesium titanate carrier.

[0120] 6) Ultrasonic dispersion of 8.5g of magnesium titanate obtained in step 5) in deionized water, heated to 40°C, to obtain solution C; dissolve 1.04g of nickel chloride and 64.1mg of ruthenium chloride in water to obtain a metal salt solution, wherein the total concentration of metal ions is 0.5mol / L; add the metal salt solution and a sodium hydroxide solution with a concentration of 2mol / L to solution C, control the pH to 8, stir for 3h, and obtain a precipitate. The obtained precipitate is washed, dried, and roasted at 600°C for 2h to obtain a roasted product. The roasted product is reduced with a mixed gas of hydrogen and nitrogen with a hydrogen gas volume fraction of 15% at 700°C for 3h to obtain 10g of catalyst. The catalyst composition and characteristic parameters are shown in Table 1.

[0121] Example 6

[0122] 1) Prepare an anhydrous ethanol-glacial acetic acid mixed solution by mixing glacial acetic acid and anhydrous ethanol in a mass ratio of 1:1.

[0123] 2) Weigh 18 g of ethyl titanate and disperse it in 107.6 g of anhydrous ethanol-glacial acetic acid mixed solution to obtain solution A.

[0124] 3) Weigh 7.7 g of magnesium nitrate and disperse it in 30.8 g of anhydrous ethanol-glacial acetic acid mixed solution to obtain solution B.

[0125] 4) Add solution B dropwise into solution A while stirring, then place in a 30°C water bath and let stand for 5 hours to obtain a sol with a pH of 3.

[0126] 5) The sol obtained in step 4) is dried at 70° C. for 24 h, and then calcined at 800° C. for 2 h to obtain a magnesium titanate carrier.

[0127] 6) Ultrasonic dispersion of 9.5 g of the magnesium titanate carrier obtained in step 5) in deionized water, heated to 40°C, to obtain solution C; dissolve 1 g of nickel chloride and 93.3 mg of ruthenium chloride in water to obtain a metal salt solution, wherein the total concentration of metal ions is 0.5 mol / L; add the metal salt solution and a sodium hydroxide solution having a concentration of 2 mol / L to solution C, control the pH to 8, stir for 3 h, and obtain a precipitate. The obtained precipitate is washed, dried, and roasted at 550°C for 2 h to obtain a roasted product. The roasted product is reduced with a mixed gas of hydrogen and nitrogen with a hydrogen gas volume fraction of 15% at 700°C for 3 h to obtain 10 g of catalyst. The catalyst composition and characteristic parameters are shown in Table 1.

[0128] Example 7

[0129] 1) Prepare an anhydrous ethanol-glacial acetic acid mixed solution by mixing glacial acetic acid and anhydrous ethanol in a mass ratio of 1:1.

[0130] 2) Weigh 26.9 g of tetrabutyl titanate and disperse it in 188.3 g of anhydrous ethanol-glacial acetic acid mixed solution to obtain solution A.

[0131] 3) Weigh 7.7 g of magnesium nitrate and disperse it in 30.8 g of anhydrous ethanol-glacial acetic acid mixed solution to obtain solution B.

[0132] 4) Add solution B dropwise into solution A while stirring, then place in a 40°C water bath and let stand for 4 hours to obtain a sol with a pH of 3.

[0133] 5) The sol obtained in step 4) was dried at 70° C. for 24 h, and then calcined at 600° C. for 4 h to obtain a magnesium titanate carrier.

[0134] 6) Ultrasonic dispersion of 8.5g of the magnesium titanate carrier obtained in step 5) in deionized water, heated to 40°C, to obtain solution C; dissolve 1.04g of nickel chloride and 64.1mg of ruthenium chloride in water to obtain a metal salt solution, wherein the total concentration of metal ions is 0.5mol / L; add the metal salt solution and a sodium hydroxide solution with a concentration of 2mol / L to solution C, control the pH to 8, stir for 3h, and obtain a precipitate. The obtained precipitate is washed, dried, and roasted at 550°C for 2h to obtain a roasted product. The roasted product is reduced with a mixed gas of hydrogen and nitrogen with a hydrogen gas volume fraction of 15% at 700°C for 3h to obtain 10g of catalyst. The catalyst composition and characteristic parameters are shown in Table 1.

[0135] Example 8

[0136] 1) Prepare an anhydrous ethanol-glacial acetic acid mixed solution by mixing glacial acetic acid and anhydrous ethanol in a mass ratio of 1:1.

[0137] 2) Weigh 26.9 g of tetrabutyl titanate and disperse it in 269 g of anhydrous ethanol-glacial acetic acid mixed solution to obtain solution A.

[0138] 3) Weigh 7.7 g of magnesium nitrate and disperse it in 30.8 g of anhydrous ethanol-glacial acetic acid mixed solution to obtain solution B.

[0139] 4) Add solution B dropwise into solution A while stirring, then place in a 30°C water bath and let stand for 7.5 hours to obtain a sol with a pH of 3.

[0140] 5) The sol obtained in step 4) was dried at 70° C. for 24 h, and then calcined at 600° C. for 2 h to obtain a magnesium titanate carrier.

[0141] 6) Ultrasonic dispersion of 8.5g of the magnesium titanate carrier obtained in step 5) in deionized water, heated to 40°C, to obtain solution C; dissolve 1.04g of nickel chloride and 64.1mg of ruthenium chloride in water to obtain a metal salt solution, wherein the total concentration of metal ions is 0.5mol / L; add the metal salt solution and a sodium hydroxide solution with a concentration of 2mol / L to solution C, control the pH to 9, stir for 3h, and obtain a precipitate. The obtained precipitate is washed, dried, and roasted at 550°C for 2h to obtain a roasted product. The roasted product is reduced with a mixed gas of hydrogen and nitrogen with a hydrogen gas volume fraction of 20% at 800°C for 3h to obtain 10g of catalyst. The catalyst composition and characteristic parameters are shown in Table 1.

[0142] Example 9

[0143] 1) Prepare an anhydrous ethanol-glacial acetic acid mixed solution by mixing glacial acetic acid and anhydrous ethanol in a mass ratio of 1:1.

[0144] 2) Weigh 26.9 g of tetrabutyl titanate and disperse it in 188.3 g of anhydrous ethanol-glacial acetic acid mixed solution to obtain solution A.

[0145] 3) Weigh 7.7 g of magnesium nitrate and disperse it in 92.4 g of anhydrous ethanol-glacial acetic acid mixed solution to obtain solution B.

[0146] 4) Add the solution from step B dropwise into solution A while stirring, then place in a 30°C water bath and let stand for 0.5 h to obtain a sol with a pH of 3.

[0147] 5) The sol obtained in step 4) was dried at 70° C. for 24 h, and then calcined at 600° C. for 2 h to obtain a magnesium titanate carrier.

[0148] 6) Ultrasonic dispersion of 8.5g of the magnesium titanate carrier obtained in step 5) in deionized water, heated to 40°C, to obtain solution C; dissolve 1.04g of nickel chloride and 64.1mg of ruthenium chloride in water to obtain a metal salt solution, wherein the total concentration of metal ions is 0.5mol / L; add the metal salt solution and a sodium hydroxide solution with a concentration of 2mol / L to solution C, control the pH to 8, stir for 3h, and obtain a precipitate. The obtained precipitate is washed, dried, and roasted at 550°C for 2h to obtain a roasted product. The roasted product is reduced with a mixed gas of hydrogen and nitrogen with a hydrogen gas volume fraction of 15% at 700°C for 3h to obtain 10g of catalyst. The catalyst composition and characteristic parameters are shown in Table 1.

[0149] Example 10

[0150] 1) Prepare an anhydrous ethanol-glacial acetic acid mixed solution by mixing glacial acetic acid and anhydrous ethanol in a mass ratio of 2.3:1.

[0151] 2) Weigh 26.9 g of tetrabutyl titanate and disperse it in 188.3 g of anhydrous ethanol-glacial acetic acid mixed solution to obtain solution A.

[0152] 3) Weigh 7.7 g of magnesium nitrate and disperse it in 153.9 g of anhydrous ethanol-glacial acetic acid mixed solution to obtain solution B.

[0153] 4) Add solution B dropwise into solution A while stirring, then place in a 30°C water bath and let stand for 1 hour to obtain a sol with a pH of 2.3.

[0154] 5) The sol obtained in step 4) was dried at 70° C. for 24 h, and then calcined at 600° C. for 2 h to obtain a magnesium titanate carrier.

[0155] 6) Ultrasonic dispersion of 8.5g of the magnesium titanate carrier obtained in step 5) in deionized water, heated to 40°C, to obtain solution C; dissolve 1.04g of nickel chloride and 64.1mg of ruthenium chloride in water to obtain a metal salt solution, the total concentration of metal ions of which is 0.5mol / L; add the metal salt solution and a sodium hydroxide solution with a concentration of 2mol / L to solution C, control the pH to 8, stir for 3h, and obtain a precipitate. Wash, dry, and roast the precipitate obtained in step 8) at 550°C for 2h to obtain a roasted product. Reduce the roasted product with a mixed gas of hydrogen and nitrogen with a hydrogen gas volume fraction of 15% at 700°C for 3h to obtain 10g of catalyst. Catalyst composition and characteristic parameters are shown in Table 1.

[0156] Embodiment 11

[0157] The method of Example 1 is followed, except that in 1), glacial acetic acid and anhydrous ethanol are prepared in a mass ratio of 2:1 to obtain an anhydrous ethanol-glacial acetic acid mixed solution, so that the pH of the sol is 2.5. A catalyst is obtained. The catalyst composition and characteristic parameters are shown in Table 1.

[0158] Example 12

[0159] The method of Example 1 was followed, except that the water bath temperature in 4) was 50° C. to obtain a catalyst. The catalyst composition and characteristic parameters are shown in Table 1.

[0160] Example 13

[0161] The method of Example 1 is followed, except that the magnesium titanate carrier is prepared by a method of the prior art, specifically comprising:

[0162] 1) Weigh 25.5 g of tetrabutyl titanate and disperse it in 61.9 g of glacial acetic acid to obtain solution A.

[0163] 2) Weigh 7.3 g of magnesium nitrate and disperse it in 61.9 g of anhydrous ethanol to obtain solution B.

[0164] 3) Add solution A dropwise into solution B while stirring, then place in a 30°C water bath and allow to stand to obtain a sol.

[0165] 4) The sol obtained in step 3) was dried at 70° C. for 24 h, and then calcined at 600° C. for 2 h to obtain a magnesium titanate carrier.

[0166] The catalyst composition and characteristic parameters are shown in Table 1.

[0167] Comparative Example 1

[0168] The method of Example 1 was followed, except that instead of using magnesium titanate as a carrier, titanium dioxide was used as a carrier, namely:

[0169] 8.5g of titanium dioxide was ultrasonically dispersed in deionized water and heated to 40°C to obtain a base solution; 3.15g of nickel chloride and 146.6mg of ruthenium chloride were dissolved in water to obtain a metal salt solution with a total metal ion concentration of 0.5mol / L; the metal salt solution obtained in step 2) and a sodium hydroxide solution with a concentration of 2mol / L were added to the base solution obtained in step 1), the pH was controlled to 8, and stirred for 3h to obtain a precipitate. The precipitate obtained in step 3) was washed, dried, and roasted at 550°C for 2h to obtain a roasted product. The roasted product was reduced with a mixed gas of hydrogen and nitrogen with a hydrogen gas volume fraction of 15% at 700°C for 3h to obtain 10g of catalyst. The catalyst composition and characteristic parameters are shown in Table 1.

[0170] Comparative Example 2

[0171] The method of Example 2 is followed, except that instead of using magnesium titanate as a carrier, titanium dioxide is used as a carrier, that is:

[0172] 8.5g of titanium dioxide was ultrasonically dispersed in deionized water and heated to 40°C to obtain a base solution; 2.1g of nickel chloride and 97.7mg of ruthenium chloride were dissolved in water to obtain a metal salt solution with a total metal ion concentration of 0.5mol / L; the metal salt solution and a sodium hydroxide solution with a concentration of 2mol / L were added to the obtained base solution, the pH was controlled to 8, and stirred for 3h to obtain a precipitate. The obtained precipitate was washed, dried, and roasted at 550°C for 2h to obtain a roasted product. The roasted product was reduced with a mixed gas of hydrogen and nitrogen with a hydrogen volume fraction of 15% at 700°C for 3h to obtain 10g of catalyst. The catalyst composition and characteristic parameters are shown in Table 1.

[0173] Comparative Example 3

[0174] The method of Example 1 was followed, except that in 3), instead of adding magnesium nitrate, an equal mole of barium nitrate was added to obtain 10 g of catalyst. The catalyst composition and characteristic parameters are shown in Table 1.

[0175] Table 1

[0176]

[0177]

[0178] Note: In the catalyst, the balance is magnesium titanate carrier.

[0179] Test Example 1

[0180] The activity of the catalyst was evaluated at different temperatures using ammonia nitrogen gas with an ammonia concentration of 15% by volume. 1 g of 40-60 mesh catalyst and 4 g of 40-60 mesh quartz sand were mixed and loaded. The volume space velocity was 15000 mL / (g·h). The results of the reaction for 6 h are shown in Table 2.

[0181] Table 2

[0182]

[0183] It can be seen from the results in Table 2 that, under the same reaction conditions, the application of the catalyst of the present invention in the ammonia decomposition hydrogen production reaction has a significantly higher ammonia decomposition conversion rate.

[0184] At the same time, compared with the comparative example, the example has a significantly higher ammonia decomposition conversion rate at 500° C., indicating that the catalyst of the present invention has a higher ammonia decomposition activity at low temperatures.

[0185] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A magnesium titanate-containing catalyst, characterized in that: The catalyst contains a magnesium titanate carrier and an active component, wherein the active component includes a noble metal and a non-noble metal, wherein the non-noble metal is selected from metal elements of Group VIII; based on the total weight of the catalyst, the content of the active component is 0.5-20% by weight in terms of the metal element; Wherein, calculated on the basis of metal elements, the mass ratio of the precious metal to the non-precious metal is 1:5-25.

2. The catalyst according to claim 1, wherein The content of the active component is 1-15% by weight, calculated as metal element, based on the total weight of the catalyst; Preferably, calculated on the basis of metal elements, the mass ratio of the noble metal to the non-noble metal is 1:10-20.

3. The catalyst according to claim 1 or 2, wherein The noble metal is ruthenium and / or palladium; Preferably, the non-precious metal is nickel.

4. A method for preparing a magnesium titanate-containing catalyst, the method comprising the following steps: S1, dissolving a titanium source in an alcohol-glacial acetic acid mixed solution to obtain a solution A; S2, dissolving the magnesium source in an alcohol-glacial acetic acid mixed solution to obtain solution B; S3, adding solution B to solution A, and then treating to obtain a sol, wherein the pH of the sol is 1.5-5; S4, drying and first calcining the sol obtained in step S3 to obtain a magnesium titanate carrier; S5. Loading active components on a magnesium titanate carrier, wherein the active components include noble metals and non-noble metals, and the non-noble metals are selected from Group VIII metal elements.

5. The method according to claim 4, wherein: In S1, the mass ratio of the titanium source to the alcohol-glacial acetic acid mixed solution is 1:2-15, preferably 1:4-10; Preferably, the titanium source is a water-soluble titanium-containing compound, preferably at least one selected from tetrabutyl titanate, ethyl titanate and isopropyl titanate; Preferably, in S2, the mass ratio of the magnesium source to the alcohol-glacial acetic acid mixed solution is 1:4-20, preferably 1:4-15; Preferably, the magnesium source is a soluble magnesium salt, preferably at least one selected from magnesium nitrate, magnesium sulfate and magnesium chloride; Preferably, in the alcohol-glacial acetic acid mixed solution of S1 and S2, the mass ratio of glacial acetic acid to alcohol is independently 1:0.1-2, preferably 1:1-2; Preferably, the alcohols in S1 and S2 are each independently a C1-C5 alcohol, preferably at least one selected from methanol, ethanol and propanol.

6. The method according to claim 4, wherein: In S3, the pH of the sol is 3-5; Preferably, the treatment conditions include: temperature of 30-50°C, preferably 30-40°C; time of 0.5-10h, preferably 0.5-8h; Preferably, in S4, the drying conditions include: a temperature of 70-100° C. and a time of 8-48 hours; Preferably, in S4, the first calcination conditions include: a temperature of 600-1000° C. and a time of 2-6 hours.

7. The method according to any one of claims 4 to 6, wherein: In S5, the active component is loaded on the magnesium titanate support by a coprecipitation method; Preferably, the coprecipitation method in S5 comprises: mixing an aqueous solution containing an active component salt, a suspension containing a magnesium titanate carrier and an alkaline solution to obtain a solid product, and then drying and second calcining the solid product; Preferably, the reaction conditions include: temperature of 40-70°C, time of 3-8h, pH of 8-10; Preferably, the conditions for the second calcination include: a temperature of 550-780° C. and a time of 2-5 hours.

8. The method according to claim 7, wherein: The active component salts include non-noble metal salts and noble metal salts; Preferably, the amount of the active component salt is such that the content of the active component in the prepared catalyst is 0.5-20% by weight, preferably 1-15% by weight, calculated as the metal element, based on the total weight of the catalyst; Preferably, the amount of the non-precious metal salt and the precious metal salt is such that in the prepared catalyst, the mass ratio of the precious metal to the non-precious metal, calculated as metal elements, is 1:5-25, preferably 1:10-20; Preferably, the noble metal is ruthenium and / or palladium; Preferably, the non-precious metal is nickel.

9. The method according to claim 7, wherein: The method further comprises: reducing the product of the second calcination to obtain the catalyst; Preferably, the reduction conditions include: temperature of 600-800°C and time of 1-3h; Preferably, the reduction is carried out in a reducing gas, the reducing gas comprising hydrogen and optionally an inert gas; in the reducing gas, the volume content of hydrogen is 10-100%; Preferably, the inert gas is selected from at least one of nitrogen, helium, argon and neon.

10. Use of the magnesium titanate-containing catalyst according to any one of claims 1 to 3 or the magnesium titanate-containing catalyst prepared by the preparation method according to any one of claims 4 to 9 in hydrogen production by decomposing ammonia.

11. A method for producing hydrogen by decomposing ammonia, the method comprising: contacting ammonia with a catalyst under conditions that decompose ammonia; Wherein, the catalyst is the catalyst according to any one of claims 1 to 3 or the magnesium titanate-containing catalyst prepared by the preparation method according to any one of claims 4 to 9; Preferably, the conditions for decomposing ammonia include: a temperature of 500-650° C. and a volume space velocity of 5000-20000 mL / (g·h).

Citation Information

Patent Citations

  • Ru-based catalyst for hydrogen production through ammonia decomposition as well as preparation and application methods of Ru-based catalyst

    CN115920942A

  • Application of nano magnesium titanate used as solid-phase extraction adsorption medium in heavy metal ion enrichment

    CN102218224A

  • Catalyst, and preparation method and application thereof

    CN110270341A

  • Supported catalyst for ammonia decomposition and preparation method thereof

    CN113694922A

  • Perovskite type catalyst and preparation method and application thereof

    CN115779895A